The Migration and Remittances Factbook 2008 - World Bank (Washington, DC : World Bank, 2012)
This fact book for 2008 attempts to present numbers and facts behind the stories of international migration and remittances, drawing on authoritative, publicly available data. It provides a snapshot of statistics on immigration, emigration, skilled emigration, and remittance flows for 194 countries and 13 regional and income groups. The top migrant destination countries are the United States, the Russian Federation, Germany, Ukraine, and France. The top immigration countries, relative to population, are Qatar (78 percent), the United Arab Emirates (71 percent), Kuwait (62 percent), Singapore (43 percent), Israel (40 percent), and Jordan (39 percent). The authors have attempted to present the best possible data in the Fact book, drawing on authoritative sources. However, the user is advised to take note of the pitfalls of using currently available migration and remittances data. Remittance flows and the stock of migrants may be underestimated due to the use of informal remittance channels, irregular migration, and ambiguity in the definition of migrants (foreign born versus foreigner, seasonal versus permanent). Considerably more effort is needed to improve the quality of data.